Identification and characterization of neutralization epitopes at VP2 and VP1 of enterovirus A71. Issue 6 (12th March 2018) - NikNadia, NMN; Tan, Chee Wah; Ong, Kien Chai; Sam, I‐Ching; Chan, Yoke Fun
Abstract : Enterovirus A71 (EV‐A71) neutralization escape mutants were generated with monoclonal antibody MAB979 (Millipore). The VP2‐T141I and VP1‐D14N substitutions were identified. Using reverse genetics, infectious clones with these substitutions were constructed and tested by neutralization assay with immune sera from mice and humans. The N‐terminus VP1‐14 is more important than EF loop VP2‐141 in acute human infection, mainly because it recognised IgM present in acute infection. The N‐terminus VP1 could be a useful target for diagnostics and therapeutic antibodies in acute infection.